The mediating role of attachment and anger: exploring the impact of maternal early-life maltreatment on child abuse potential - Wuebken, Karolina; Bermpohl, Felix; Boedeker, Katja; Hindi Attar, Catherine; Kluczniok, Dorothea; Schoofs, Nikola; Fuchs, Anna; Neukel, Corinne; Herpertz, Sabine C.; Brunner, Romuald; Winter, Sibylle Maria; Kaess, Michael; et al. (Frontiers in Psychiatry, 2023)
Background: Maternal early-life maltreatment (ELM) increases the risk of subsequent child maltreatment, but the underlying mechanisms of these intergenerational effects remain largely unknown. Identifying these mechanisms is crucial for developing preventive interventions that can break the cycle of abuse. Notably, previous research has shown that ELM often results in attachment insecurity and altered anger characteristics. Therefore, this study determines whether these characteristics mediate the relationship between maternal history of ELM and child abuse potential. Methods: The study sample included 254 mothers, of whom 149 had experienced ELM to at least a moderate degree. Maternal ELM was assessed using the Childhood Experience of Care and Abuse (CECA) interview. Attachment insecurity, trait anger and anger expression, and maternal abuse potential were assessed using the Vulnerable Attachment Questionnaire (VASQ), State-Trait Anger Expression Inventory (STAXI), and Child Abuse Potential Inventory (CAPI), respectively. Results: The severity of maternal ELM predicted higher child abuse potential, with attachment insecurity and anger suppression mediating this effect. Specifically, higher levels of maternal ELM were associated with greater attachment insecurity and increased anger suppression, resulting in a higher child abuse potential. Although higher levels of trait anger were directly associated with higher child abuse potential, this parameter did not mediate the relationship with ELM. In addition, no significant associations were observed between outwardly expressed anger and ELM or child abuse potential. All analyses were adjusted for maternal mental disorders, years of education, and relationship status. Discussion: Attachment insecurity and anger suppression may serve as pathways linking the maternal history of ELM to the risk of child abuse, even when considering maternal psychopathology. Overall, our findings indicate that interventions aimed at strengthening attachment and improving anger suppression may be beneficial for all mothers with ELM history and high child abuse potential, not just those who suffer from mental illness.